Folk Knowledge of an Individual Plant Specimen: The Case of the Royal Fern (Osmunda regalis L.) in Virestad Parish, Småland, Sweden - Svanberg, Ingvar (Ethnobiology Letters, 2012)
Ethnobiological studies of local economic or folk religious uses of plants often rely on the assumption that plant use relates to folk knowledge about specific taxa. However, in some cases, folk knowledge is more about beliefs concerning an individual plant. When Carl Linnaeus traveled in 1749 through his native province of Småland, Sweden, he observed a striking specimen of a royal fern (Osmunda regalis L.), which was being used by a local healer. The appearance and unusually large size of this individual plant specimen were possibly responsible for its use. This species has not been used elsewhere in Sweden and historical data refer only to the single specimen observed by Linnaeus.